Ariadne's thread : the search for new modes of thinking - Clark, Mary E. ([S.l.] : Palgrave Macmillan, 1989)
This book is a powerful, interdisciplinary introduction to environmental studies.
Keywords: Civilization, Modern; Twentieth century; Twenty-first century